2016
DOI: 10.1002/bmc.3756
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the interactions between Chrysanthemum morifolium flowers extract and intestinal bacteria from human and rat

Abstract: Flos Chrysanthemi, dried flower of Chrysanthemum morifolium Ramat, has drawn much attention recently owing to its potential beneficial health effects for human. Flos Chrysanthemi products are usually taken orally and metabolized by intestinal microflora. However, there has been no investigation of the comprehensive metabolic profile of the Flos Chrysanthemi extract by intestinal flora owing to its chemical complexity and the limitations of analytical methods. In this paper, a rapid, sensitive and automated ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Compared with other studies on metabolic differences between species (Lattanzio et al, 2011; Meyer et al, 2010), two reasons might be responsible for our results. First, the metabolic enzymes differ between the two species, such as CYP1A1 and CYP3A4 for intestinal bacteria (Hagenauer et al, 2001; Tao et al, 2016; Xue et al, 2011). Second, the transporters in the liver and intestinal cell membrane are different.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with other studies on metabolic differences between species (Lattanzio et al, 2011; Meyer et al, 2010), two reasons might be responsible for our results. First, the metabolic enzymes differ between the two species, such as CYP1A1 and CYP3A4 for intestinal bacteria (Hagenauer et al, 2001; Tao et al, 2016; Xue et al, 2011). Second, the transporters in the liver and intestinal cell membrane are different.…”
Section: Resultsmentioning
confidence: 99%
“…[ 37 ]. Previous in vitro study found that ethanol extract from C. morifolium flowers inhibited the growth of certain pathogenic bacteria but moderately promoted the growth of commensal probiotics such as Lactobacillus and Bifidobacterium [ 16 ]. A further study demonstrated that oral administration of polysaccharides from C. morifolium could be an effective treatment for ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin, a major component of C. morifolium extract, has been extensively studied for its anti-inflammatory, antibacterial effects, and its ability to alleviate LPS-induced liver damage by inhibiting oxidative stress and inflammation [ 15 ]. In addition, ethanol extract from C. morifolium flowers has been shown to inhibit the growth of pathogenic bacteria in vitro [ 16 ], while the aqueous extract from the flower heads of C. morifolium displayed its anti-inflammation effect in macrophages [ 17 ]. However, there is a lack of studies on their impacts on gut microbiota, and the function of aqueous extract from C. morifolium flowers on glucose metabolism is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has reported that two active substances obtained from flowers of Lonicera japonica , 7-acetyl-8,9-dihydroxy thymol, and 7,8-dihydroxy-9-buyryl thymol play antibacterial effects on Staphylococcus aureus , Escherichia coli , Micrococcus luteus , and Bacillus cereus [ 26 , 27 ]. Chrysanthemum morifolium extract represses the growth of different intestinal pathogenic bacteria, such as Enterobacter , Enterococcus , Clostridium , and Bacteroides [ 28 ]. The bioactive compounds aloe emodin, aloe-emodin acetate, and 5 α ,8 α -epidioxy-24(R)-methylcholesta-6,22-dien-3 β -ol and p-hydroxyl benzyl acid, extracted from Siraitia grosvenorii leaves limits the growth of oral bacterial species S .mutans , Actinobacillus actinomycetemcomitans , Fusobacterium nucleatum , and the yeast Candida albicans [ 29 ].…”
Section: Discussionmentioning
confidence: 99%